Strata zdrowia i jej wartościowanie w prozie epistolarnej Joachima Lelewela adresowanej do najbliższych = Loss of health and its valuation in Joachim Lelewel`s epistolary prose addressed to loved ones - Jaros, Violetta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This sketch is a supplement to the text entitled "The Brussels Loner Privately. Vocabulary related to illness and disease phenomena in Joachim Lelewel`s correspondence with his loved ones" and is intended not only to unveil the scholar`s daily struggles with the weaknesses of his body and the associated handicaps and exclusion, healing practices and actions taken against his body, but above all his attitude to the loss of his own or other people`s health and the ways of externalizing it, which involves the concept of valuing, which in the case of the letters under study combines an individual, subjective approach with a supra-individual one common to entire human communities.
Keywords: Lelewel, Joachim (1786-1861); choroba; wartościowanie; list; illness; valuing; letter